The Structure of Game Design - Wang, Wallace (Cham : Springer International Publishing : Imprint: Springer, 2023)
The Structure of Game Design is designed to help aspiring and existing game designers turn their ideas into working games. Creating a game involves understanding the core foundational elements of all types of games from paper-based games to the latest video games. By understanding how these core principles work in all types of games, you can apply these same principles to design your own game. Games are about goals, structure, play and fun. While everyone will always have their own idea of what might be "fun", any game designer can maximize player enjoyment through meaningful choices that offer various risks and rewards. Such challenges, combined with rules and limitations, force players to overcome obstacles and problems using a variety of skills including dexterity, puzzle solving, intelligence, and strategy. Essentially games allow players to venture forth into new worlds and overcome problems in a safe but exciting environment that allows them to triumph in the end. Just as playing games have proven popular around the world to all ages, genders, and cultures, so has game designing proven equally popular. Games can challenge players to make the best move, solve puzzles, engage in combat, manage resources, and tell stories. By understanding how randomness, psychology, and balance can change the way games play, readers can decide what game elements are best for their own game creation. Whether your goal is to make money, learn something new, make a social statement, improve on an existing game idea, or challenge your artistic, programming, or design skills, game design can be just as much fun as game playing. By knowing the parts of a game, how they work, how they interact, and why they're fun, you can use your knowledge to turn any idea into a game that others can play and enjoy.
Creating a Game Idea -- Defining a Game Idea -- The Appeal of Games -- Game Design Elements -- Understanding Game Loops -- Randomness in Games -- Psychology in Games -- Game Balance -- Understanding Fun -- Fun in Movement -- Fun in Puzzles -- Fun in Combat -- Fun in Strategy -- Fun in Economics -- Fun in Storytelling -- Turning a Game Idea Into a Real Game -- Prototyping -- Card Game Prototypes -- Understanding Game Engines -- Playing Field Prototypes -- Level Design Prototypes -- Movement Prototypes -- Combat Prototypes -- Resource Management Prototypes -- Puzzle Prototypes -- Selling a Game to the Market.
Keywords: Computer games -- Programming; Multimedia systems; User interfaces (Computer systems).; Human-computer interaction; Game Development; Multimedia Information Systems; User Interfaces and Human Computer Interaction